First record of Mansoa minensis M.M.Silva-Castro (Bignoniaceae, Bignonieae) in Espírito Santo, Brazil - Udulutsch, Renata Giassi [UNESP]; Siqueira, Geovane Souza; Dias, Pedro (Pensoft Publishers, 2018)
Mansoa minensis M.M.Silva-Castro is reported for the first time for the state of Espírito Santo, Brazil. We provide an updated description, comparisons with closely related species, and suggest a revised conservation status for this species. We also present an identification key for all species of Mansoa that occur in Espírito Santo.
Keywords: Atlantic forest; Endemism; IUCN categories